PENGARUH MANAJEMEN LABA AKRUAL DAN RIIL PADA KINERJA KEUANGAN - Sri Ruwanti, Prima Aprilyani Rambe (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2017)
The objective of this study is investigate effect of earnings management to financial performance. Two proxy was used in this study, they are discretionary accruals and real earnings management. Return on Assets as proxy of financial performance. There are 126 manufacture firms as population and 46 firms as samples used purposive sampling method. Result show that discretionary accruals has influence to financial performance, but not for real earnings management.